Utilisation of Image Guidance to Enhance Safety of Deployment of the Mynx Control Vascular Closure Device. (November 2021) - Dolan, Steven G.; Mulholland, Douglas; Thulasidasan, Narayanan; Diamantopoulos, Athanasios
The Mynx Control device (Cardinal Healthcare, Dublin, Ohio, USA) was recently licensed and allows for entirely extravascular arteriotomy closure. It uses a polyethylene glycol sealant plug which is absorbed fully within 30 days, alleviating concerns around difficulties with regaining access in future. The Mynx device uses a balloon, inflated within the artery and retracted against the arteriotomy to achieve haemostasis, with the extravascular sealant plug then deployed outside the vessel wall. While the manufacturer's instructions for use do not include utilisation of imaging guidance, we routinely employ fluoroscopic and/or ultrasound to ensure safe use of the device. These techniques allow confirmation of balloon position against the arteriotomy, hence avoiding inadvertent deployment of the plug partially or fully intraluminally. Visualisation of the balloon within the lumen also eliminates risk of plaque disruption in diseased vessels on retraction of the device. Image guidance adds little time to device deployment, and the safety benefits are such that we recommend that practitioners elsewhere consider adopting our techniques. Here, we describe the process involved in both techniques.